Polycystic ovary syndrome awareness: insights from female medical students in Telangana - Gajula, Sai Karthik; Firdous, Humera; Sudhir, Sunita; Gurrapu, Rakesh (International Journal Of Community Medicine And Public Health, 2026)
Background: Polycystic ovary syndrome (PCOS) affects millions of young women worldwide, yet awareness remains suboptimal even in medical trainees. This study explored the knowledge, attitudes, and practices (KAP) regarding PCOS among 320 female medical students in Telangana, India, a group particularly vulnerable due to academic stress, irregular lifestyles, and limited personal health prioritization. Methods: A validated, web-based cross-sectional survey was conducted among undergraduate and postgraduate female medical students aged 18–30 years. KAP scores were categorized as low (<37), moderate (38–45), or high (>45) using visual binning. Associations with age, menstrual regularity, BMI, stress levels, and PCOS diagnosis were analyzed using chi-square tests and independent t-tests. Results: Most participants (63.1%) showed moderate KAP, 24.1% low, and only 12.8% high. Higher KAP was significantly associated with older age (p=0.016), menstrual irregularity (p=0.029), and previous PCOS diagnosis (p<0.001). Students diagnosed with PCOS reported significantly higher stress levels (mean 3.30 versus 2.99, p=0.007). BMI was significantly linked to PCOS diagnosis (p=0.015). Conclusions: Moderate levels of PCOS awareness have been recorded with personal diagnosis being the strongest driver of knowledge. The elevated stress among affected students highlights the emotional burden of the condition. These findings emphasize the need for structured PCOS education, early screening, and psychosocial support within medical curricula to empower future physicians to better care for themselves and their patients.